Negotiating culture and human rights - Bell, Lynda Schaefer; Nathan, Andrew J. (Andrew James); Peleg, Ilan, 1944- (Columbia University Press, 2001)
"Negotiating Culture and Human Rights provides a new interdisciplinary approach to issues of cultural values and universal human rights. Central to the discussion is the "Asian values debate," so named because of the culturally relativist ideals embraced by some key Asian governments. By analyzing how cultural difference and human rights operate in theory and practice in such areas as legal equality, women's rights, and ethnicity, the contributors forge a new way of looking at these critical issues. They call their approach "chastened universalism," arguing that respect for others' values need not lead to sterile, relativist views. Ultimately the authors conclude that it is less important to discover pre-existing common values across cultures than to create them through dialogue and debate."--Book cover